Identifying Factors Influencing Sanitation Condition in Homes within Jatisari Urban Village, Semarang City - Lutfyana Herawati; Yuni Wijayanti (Universitas Diponegoro, 2024)
The condition of the sanitation environment within households is a crucial aspect of community health, ensuring the adoption of behaviors conducive to cleanliness and well-being. Inadequate sanitation conditions within homes pose risks and facilitate the transmission of various diseases. This research aims to explore factors associated with household sanitation conditions, including knowledge, attitudes, income, and education. The study employs an observational analytics approach, utilizing a cross-sectional design. The sample comprises 95 respondents, with research instruments including questionnaires and observational sheets. Data analysis involves both univariate and bivariate analyses, utilizing chi-square tests. Univariate analysis reveals that 42 respondents (44.2%) possess good knowledge, 48 (50.5%) exhibit positive attitudes, 54 (56.8%) have higher education levels, and 53 (55.8%) earn less than Rp. 3,060,000. Moreover, 80 respondents (84.2%) have adequate sanitation conditions at home. Bivariate analysis demonstrates significant relationships between knowledge (p = 0.000), attitude (p = 0.022), income (p = 0.019), education (p = 0.018), and household sanitation conditions. The findings suggest that enhancing awareness and promoting hygiene practices among the residents of Jatisari Village, Semarang City, can mitigate disease transmission and improve overall community health.